"I feel like I am a hybrid myself": An Interview with Professor Peter Burke (University of Cambridge) - Čapská, Veronika (Dějiny – teorie – kritika, 2021)
Professor Peter Burke of Emmanuel College, University of Cambridge, has been a major influence in shaping cultural history as a research field by promoting innovative approaches, expressing a constant desire, or perhaps need, to open history up to neighbouring disciplines, mainly cultural anthropology, sociology and visual studies. This conversation between DTK’s Editor-in-Chief, Veronika Čapská, and Peter Burke was recorded on June 11th 2019 in the welcoming environment of Trinity Hall at the University of Cambridge. The dialogue focuses on new research trends, many of which react to contemporary societal challenges.